Patterns of adversity and post-traumatic stress among children adopted from care. (August 2022) - Anthony, R.; Paine, A.L.; Westlake, M.; Lowthian, E.; Shelton, K.H.
Abstract: Background: Children adopted from care are more likely to have experienced early adversity, but little is known about the impact of early adversity on later post-traumatic stress (PTS) symptoms. Objective: To investigate sub-groups of adversity in a sample of adopted children and examine the association with later PTS symptoms. Participants and setting: A study of British children adopted from care using social worker records ( N = 374) and questionnaire-based longitudinal study of n = 58 children over 4-years post adoptive placement. Methods: We used latent class analysis to identify subgroups of children based on commonalities in perinatal and postnatal adversity experienced prior to adoption and examined differences in PTS symptoms at 4-years post-placement between subgroups. Results: Nearly one in five (19 %) children were in the clinical or borderline ranges for symptoms of PTS arousal, 14 % for PTS avoidance and 8 % for PTS intrusion. The 5-class solution fitted the data best, with one class characterized by children with a low probability of experiencing any adversity, one perinatal adversity class and three classes capturing different patterns of adversity. The multiple complex adversity class involving both perinatal and postnatal adversity had significantly higher symptoms of PTS avoidance and arousal than other sub-groups. Conclusions: The prevalence and complexity of PTS symptoms among adoptive children highlights the need for effective interventions considering different profiles of early adversity.